Calcium channels and iron uptake into the heart - Chattipakorn N. (2014)
Iron overload can lead to iron deposits in many tissues, particularly in the heart. It has also been shown to be associated with elevated oxidative stress in tissues. Elevated cardiac iron deposits can lead to iron overload cardiomyopathy, a condition which provokes mortality due to heart failure in iron-overloaded patients. Currently, the mechanism of iron uptake into cardiomyocytes is still not clearly understood. Growing evidence suggests L-type Ca(2+) channels (LTCCs) as a possible pathway for ferrous iron (Fe(2+)) uptake into cardiomyocytes under iron overload conditions. Nevertheless, controversy still exists since some findings on pharmacological interventions and those using different cell types do not support LTCC's role as a portal for iron uptake in cardiac cells. Recently, T-type Ca(2+) channels (TTCC) have been shown to play an important role in the diseased heart. Although TTCC and iron uptake in cardiomyocytes has not been investigated greatly, a recent finding indicated that TTCC could be an important portal in thalassemic hearts. In this review, comprehensive findings collected from previous studies as well as a discussion of the controversy regarding iron uptake mechanisms into cardiomyocytes via calcium channels are presented with the hope that understanding the cellular iron uptake mechanism in cardiomyocytes will lead to improved treatment and prevention strategies, particularly in iron-overloaded patients.